The Analysis of Simple Household Water Purification - Dewi Fitria; Rahmi Julianda; Nurhaliza Nurhaliza; Nurhayati Nurhayati; Puspa Sriwujayanti (International Journal Labs, 2022)
This study aims to analyze and apply a simple water purification device for households. The research method used is the filtering method. Filtration is a method of purifying water by filtering water and using various materials such as cloth, cotton, gravel, palm fiber, and other materials to get better water quality. The results showed that you can produce clean water suitable for use with simple, easy-to-find, and relatively low-cost tools. The thicker the materials used, the cleaner the water, because the impurities contained in the water will be filtered out by the materials used in filtering.